The prevalence of non-communicable diseases and its effects on doctor visits among the elderly in Malaysia - Samsudin, Shamzaeffa; Abdullah, Norehan; Applanaidu, Shri Dewi (2015)
The prevalence of non-communicable diseases (NCDs) in Malaysia shows a rising trend that influences the society in many respects.A country specific evidence is vital for effective intervention.The aims of this study were to identify the role of gender and urbanization status on NCDs prevalence, which in this study we concentrated on diabetes and hypertension (high blood pressure) among older population in Malaysia.We extended the study with parametric analysis to find the effect of these health problems on the likelihood of doctor visits as it reflects the equity for access and utilization issues.A total of 1,414 respondents aged 60 years and above were selected using a multistage sampling for face-to-face interview. Results showed that there was a significant difference of distribution by gender for hypertension but not diabetes.The prevalence was higher at urban setting but with no significant difference.By utilizing probit model, we found that those with diabetes or hypertension, controlling for other variables, were more likely to utilize doctor services.This result implies that the prevalence of NCDs may further increase demand for health care, especially in the state with a high proportion of older age groups.